The Effect of Shopping Dependence, Consumptive Behavior on Fintech Lending with Consumer Debt Levels as Intervening Variables - Rinintha Parameswari; Fredy Perdana Putra; Rudiyanto (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
This study examines the influence of online shopping dependence and consumer behavior on online loans, with consumer debt levels as intervention variables. The background of this study is the phenomenon of increasing consumer behavior driven by the ease of online shopping, which often triggers compulsive shopping behavior. The purpose of this study is to understand how dependence on online shopping and consumer behavior affect consumer debt through the use of fintech loan services. The research method uses a descriptive quantitative approach with data collection through questionnaires from 100 respondents who use e-commerce applications and online loans. Data were analyzed using path regression analysis to determine significant relationships between the variables studied. The results show that shopping dependence and consumer behavior have a significant direct and indirect effect on consumer debt levels through online loans. This conclusion emphasizes the importance of managing shopping habits and financial behavior in overcoming consumer debt problems in the digital era. Direct Influence: Online shopping dependency (X1) has a significant effect on online loans (Y) with a beta coefficient of 0.288 and on consumer debt (Z) with a coefficient of 0.456.Consumer behavior (X2) also has a significant effect on Y (coefficient 0.626) and on Z (coefficient 0.275).Online loans (Y) have a significant effect on consumer debt (Z) with a coefficient of 0.224. Indirect Influence: The indirect effect of X1 on Z through Y is 0.0621, so the total effect is 0.50. The indirect effect of X2 on Z through Y is 0.085, with a total effect of 0.374.